COST OF ELECTRIC POWER SUPPLY AND ECONOMY CONDITIONS OF ITS TRANSMISSION IN POWER SYSTEM - G. E. Pospelov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers dependences of electric power supply cost on transferred power and reveals conditions of economical efficiency of electric power transmission in power system.